Rancang Bangun Aplikasi Tabungan Siswa Berbasis Android Pada SMA Negeri 1 Rambang - Herdi Wijaya; Khana Wijaya; Yuntari Purbasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The development of technology today is very rapid, especially in the field of information technology. With the development of increasingly advanced and rapidly developing technology, humans can make various tools and aids in carrying out various activities. Technology has also played a role in various aspects of life, one of which is education. Rambang 1 public high school is one of the senior high schools that already has complete facilities and infrastructure such as the provision of a student saving program. However, data processing on student savings still uses a manual system, which is still keeping records on books and has not been computerized which causes several obstracles in carrying out savings transactions such as frequent loss of savings books, requiring time to search student data when entering deposit transactions in large quantities requires a relatively long time. This of course will slow down a job that should be done faster. Therefore we need a computerized students savings application which is expected to help solve the problems that occur. In designing this system using the agile software development method, with UML system modeling tools, and using data collection techniques through observation, interviews, and literature study.